Space charge dynamics under AC field - Mohd Faiznazif Bin Mohd Nordin (2023)
This thesis reports the simulation of space charge dynamics in insulating polymeric cable subjected to high electric fields and its relationship to electrical aging that cause cables to degrade. Further studies suggested that space charge phenomenon is one of the factors of insulating polymeric ageing during high electrical fields transported by conductor itself. This thesis also studies about the characteristics of space charge and the mechanisms occurs subjected to degrade insulating polymeric in underground power cable. The simulation of space charge is done by using 50 Hz of ac sinusoidal waveform under uniform field.